Media Visual Tradisional vs Digital: Transformasi Pembelajaran di Era Teknologi - Sitti Fatima; Andi Abdul Hamzah (Lembaga Yasin AlSys, 2026)
Although digital technology has brought major changes to global education, studies that specifically address comparisons of the effectiveness and integration strategies of traditional and digital visual media across geographic contexts with limited infrastructure remain very limited. This study aimed to provide an in-depth analysis of the comparison between traditional and digital visual media, covering their advantages, inherent limitations, and implications for use in both general education and Islamic education settings. The study employed a descriptive-comparative qualitative approach with a literature review design, conducting a systematic analysis of diverse primary and secondary literature published over the past ten years. Data were collected through rigorous literature identification and document classification and were analyzed using a descriptive-comparative method to comprehensively synthesize findings from prior studies. The results showed that traditional visual media remain highly relevant for supporting direct interaction, value internalization, and character formation, whereas digital visual media are superior in enhancing learning motivation and the effectiveness of content delivery through dynamic visualization and high interactivity. In addition, the study identified the risks of technological dependence and declining interest in reading physical books as critical anomalies associated with the use of digital media. These findings contributed substantially to the development of instructional media theory through the formulation of a Hybrid-Visual integration model grounded in Dual Coding Theory. The study concludes that synergy between traditional and digital visual media is essential for holistic learning and suggests that educators develop digital literacy without abandoning a personal and humanistic approach. The implications include recommendations for educational institutions to continue facilitating conventional media use to support affective depth while expanding digital infrastructure that is adaptive to the needs of the digital generation.